2019
DOI: 10.5965/223811711812019212
|View full text |Cite
|
Sign up to set email alerts
|

Características físicas e sensoriais de Salame Tipo Italiano com adição de própolis

Abstract: RESUMONo presente estudo foram elaboradas quatro formulações de salame tipo italiano, sendo uma isenta de antioxidante (controle), uma adicionada de antioxidante sintético (BHT) e duas contendo extrato de própolis (0,01% e 0,05%). As amostras foram submetidas a análises microbiológicas, sensoriais e perfil de textura e cor, além da perda de peso e o pH durante o período de maturação. Os resultados mostraram perda de peso das formulações durante a maturação, indicando que a incorporação da própolis não afetou o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…The drop in humidity can interfere negatively with the texture of the salami, implanting in a greater proteolysis and consequently a greater softness in the final product, an unwanted characteristic for salami, which means that the higher force applied, the harder the texture of the product will be, which leads to less humidity and present water activity (Aw) [26,31]. The results obtained did not have significant difference between them, as well as the S2 and S3 assays, that had similar results to those of lamb meat for shear force between 3.56 kgf and 5.38 kgf [32].…”
Section: Physical and Physicochemical Analysesmentioning
confidence: 81%
“…The drop in humidity can interfere negatively with the texture of the salami, implanting in a greater proteolysis and consequently a greater softness in the final product, an unwanted characteristic for salami, which means that the higher force applied, the harder the texture of the product will be, which leads to less humidity and present water activity (Aw) [26,31]. The results obtained did not have significant difference between them, as well as the S2 and S3 assays, that had similar results to those of lamb meat for shear force between 3.56 kgf and 5.38 kgf [32].…”
Section: Physical and Physicochemical Analysesmentioning
confidence: 81%
“…Mafra et al (2019) demonstrated that a studied starter culture resisted the production conditions of a salami that used tilapia meat as a raw material, promoting an efficient reduction in pH (6.8-5.95). The acidic environment during the sausage fermentation process constitutes an obstacle to the survival of decay-causing and pathogenic microorganisms, providing microbiological stability, reducing water retention and, consequently, firm texture and feasibility to the product (Savoldi et al, 2019).…”
Section: Technological Characteristicsmentioning
confidence: 99%
“…As indústrias, especialmente do setor cárneo têm buscado utilizar produtos naturais para preservar e aumentar a vida útil de seus produtos sob o ponto de vista microbiológico e físico-químico em detrimento dos conservantes sintéticos (SAVOLDI et al, 2019).…”
Section: A Própolis Como Conservante Naturalunclassified